Mitral annular peak systolic and diastolic velocities are characteristic of healthy hearts: A Doppler tissue imaging study. Issue 3 (28th December 2018) - Simpson, Timothy F.; Tyler, Jeffrey M.; Thomas, Randell C.; Fang, Qizhi; Bibby, Dwight; Schiller, Nelson B.
Abstract : Introduction: Although systolic and diastolic dysfunction must coexist, they are most often considered in isolation. Therefore, a simple and reproducible quantitative measurement that integrates systolic and diastolic function is desirable. We hypothesize that the absolute sum of lateral mitral annular systolic and early diastolic peak velocities is predictive of overall cardiac function. Methods: In this study, lateral mitral annular systolic (S′) and early diastolic (E′) peak velocities were measured in healthy subjects and compared against subjects with progressive degrees of systolic and diastolic dysfunction. Results: A total of 149 subjects (56% male, mean age 48 years) were enrolled and stratified according to global left ventricular function: 76 normal, 40 mild‐moderate dysfunction, and 33 moderate‐severe dysfunction. Adjusting for baseline differences including age, univariate analysis showed mean S′ + E′ values were significantly different between subjects with normal, mild‐moderate, and moderate‐severe global left ventricular function (27, 17, 13 cm/s; P < 0.001 for all comparisons). The absolute sum of S′ + E′ ≥ 20 cm/s identified normal global left ventricular function with a sensitivity of 95%, specificity of 85%, and ROC area under the curve of 0.924. Conclusions: In a cohort of subjects with varying levels of combined systolic and diastolic function, the easily obtainable composite score of S′ + E′ ≥ 20 cm/s is strongly predictive of normal global left ventricular function with a high degree of sensitivity and specificity. Additional studies should be considered to expand this concept to additional populations.